2022
DOI: 10.1088/1758-5090/ac5220
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of interface printing patterns within 3D printed multilayered scaffolds for osteochondral tissue engineering

Abstract: Osteoarthritis is a highly prevalent rheumatic musculoskeletal disorder that commonly affects many joints. Repetitive joint overloading perpetuates the damage to the affected cartilage, which undermines the structural integrity of the osteochondral unit. Various tissue engineering strategies have been employed to design multiphasic osteochondral scaffolds that recapitulate layer-specific biomechanical properties, but the inability to fully satisfy mechanical demands within the joint has limited their success. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…This approach produced scaffolds with tensile and compressive mechanical properties close to those of native tissues, but limited tissue repair in vivo [ 68 ]. In addition, a computational investigation has been conducted recently at the interfaces of bilayered polymeric scaffolds, and the results showed that polycaprolactone (PCL)/gelatin methacrylate and PCL/polyethylene glycol diacrylate (PEGDA) scaffolds exhibited the best tensile, compressive and shear properties among various polymer scaffolds produced by 3D printing [ 92 ]. This insight could guide future studies on construction of polymeric bilayered scaffolds by selecting appropriate biomaterials (discussed in Section 4 ).…”
Section: Biomimetic Architectures In Mzsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach produced scaffolds with tensile and compressive mechanical properties close to those of native tissues, but limited tissue repair in vivo [ 68 ]. In addition, a computational investigation has been conducted recently at the interfaces of bilayered polymeric scaffolds, and the results showed that polycaprolactone (PCL)/gelatin methacrylate and PCL/polyethylene glycol diacrylate (PEGDA) scaffolds exhibited the best tensile, compressive and shear properties among various polymer scaffolds produced by 3D printing [ 92 ]. This insight could guide future studies on construction of polymeric bilayered scaffolds by selecting appropriate biomaterials (discussed in Section 4 ).…”
Section: Biomimetic Architectures In Mzsmentioning
confidence: 99%
“…As the integration between the osseous and chondral zones has been shown to be a critical factor influencing the treatment efficiency [ 92 , 486 ], it is one of the most indispensable needs in the future to explore more advanced strategies to improve the interfacial bonding strength between two adjacent layers within MZSs. Besides, the transition layer should have ideal porosity and pore sizes to 1) allow for nutrient and waste transportation between osseous and chondral zones; 2) prevent differentiated cells from crossing the interface; 3) act as a barrier to prevent the regenerated blood vessels and nerves of subchondral bone from invading into the articular cartilage zone; and 4) bear proper biomechanics for appropriate stress distribution.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Osteochondral defects may occur due to inflammation or osteoarthritis, which lead to damage of the cartilage and underlying bone. Unfortunately, cartilage has limited capability to self-repair, and the disease causes degradation of articular (hyaline) cartilage and narrowing of joint space. , Currently, the gold standard for treatment of osteochondral defects is surgery . Usually tissue is replaced with autografts, and bone tissue engineering implants are also used. , Cells may also be injected to the defect site without a scaffold; however, this does not work very efficiently …”
Section: Introductionmentioning
confidence: 99%
“…For osteochondral regeneration, it is urgent to prepare an integrated layered scaffold with zonally stratified mechanical properties that exhibits great mechanical distribution and good integration ability and prevents changes in microstructure and composition. In addition, improving the mechanical distribution properties of scaffolds contributes to provide a more robust mechanical microenvironment for osteochondral regeneration . The mechanical signals also play important roles in bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, improving the mechanical distribution properties of scaffolds contributes to provide a more robust mechanical microenvironment for osteochondral regeneration. 19 The mechanical signals also play important roles in bone tissue regeneration. Matrix stiffness, a physical signal in the extracellular microenvironment, can regulate stem cell lineage differentiation.…”
Section: Introductionmentioning
confidence: 99%